Effects of herpes zoster vaccination and antiviral treatment on the risk of stroke: a systematic review and meta-analysis - Jia, Yong-hui; Dong, Yu-bo; Jiang, Hai-yin; Li, Ai-juan (Frontiers in Neurology, 2023)
Background Evidence suggests that there is an increased risk for stroke after herpes zoster (HZ). However, reports on the effects of HZ vaccine and antiviral treatment on stroke risk are inconsistent. Thus, we examined these associations via meta-analysis. Methods: To identify relevant studies, we searched three databases for articles published up to January 2023. Random effects models were explored to determine overall pooled estimates and 95% confidence intervals (CIs). Results: This review included 12 observational studies (six on HZ vaccine and seven on antiviral treatment). In comparisons of vaccinated and unvaccinated patients, the vaccine was found to be associated with a lower risk for stroke (OR, 0.78; 95%CI 0.68–0.9; P=0.001). Meta-analysis of self-controlled case series (SCCS) revealed evidence for a reduced OR in individuals who received the vaccine (OR, 1.14; 95%CI 0.94–1.37; P=0.181) compared to unvaccinated individuals (OR, 1.36; 95%CI 1.15–1.61; P<0.001). Compared to untreated patients, antiviral therapy was not associated with a reduced risk for stroke (OR, 1.13; 95%CI 0.94–1.36; P=0.201). The meta-analysis of SCCS revealed no evidence for a reduced OR among individuals who received antiviral therapy (OR, 1.33; 95%CI 1.17–1.51; P<0.001) compared to untreated individuals (OR, 1.45; 95%CI 1.25–1.69; P<0.001). Conclusion: This meta-analysis suggests that the HZ vaccine, but not antiviral treatment, decreases the odds of developing stroke.